Mixed convection MHD hybrid nanofluid over a shrinking permeable inclined plate with thermal radiation effect - Wahid, Nur Syahirah; Arifin, Norihan Md; Khashi'ie, Najiyah Safwa; Pop, Ioan (Elsevier, 2023)
In many applications, hybrid nanofluids showed superior heat transfer outcomes; nevertheless, further study is needed to expand the range of applications for hybrid nanofluids. Therefore, in this study, the radiative magnetohydrodynamic (MHD) mixed convective aluminacopper/water hybrid nanofluid flow past an inclined shrinking plate is analyzed. By incorporating similarity transformations, the PDEs of the flow model is converted to ODEs. The boundary value problem of the fourth-order accuracy code (bvp4c) is implemented to solve the mathematical model numerically. When preliminary assumptions are appropriate, the above-proposed method may provide non-unique outcomes. Due to the plate’s shrinking motion, two solutions are possible. The first solution is stable based on a stability study. Therefore, we only rely on the first solution for effective practical uses. The findings reported that using less copper concentration (1 volume fraction instead of 2 ) and applying more thermal radiation and MHD effect, the heat transfer rate might increase significantly when the plate is inclined considerably (at 70 degrees). It is possible to avoid the flow separation by upsurging the copper volume fraction from 1 to 2 at a higher MHD effect. The boundary layer separation is not affected by the employment of various inclination angles, variable thermal radiation, and mixed convection. This study offers valuable insight into fundamental transport phenomena such as the transmission of heat, momentum, or mass. Thus, it provides valuable information on the gradients of essential factors to control the boundary layer flow pattern.